Participatory approach for water security: a methodological inquest based on stakeholders’ perspectives, nallur ds division - Srikanthan, S.; Jeevasuthan, S. (University of Jaffna, 2021)
This study attempts to discuss the methodological review on the application of participatory approach in the project on water security in Northern Province. The thought on water security appeared as a new perspective to treat the water related matters in a holistic view instead of the themes such as water issue, water pollution, and water management in the beginning of 1990. Participatory approach is widely applied in the health and social science fields to achieve real outcome in their research and project activities. This project on water security is also based on participatory action research. This study explores on what are the benefits of using participatory approach in this project and in which ways it helps to direct the future plans of the project. The world café method was used to organize the meeting with various participants of research area at one place in various times. The types of participants were: Officials from the Government sector, relevant non – state actors, trade people, activists, media persons, educators, researchers, school students and teachers and typology of participants are not confined to these categories. The organized meeting with the stakeholders belong to the Nallur DS Division opened a platform to discuss on various aspects of water security in Northern Province based on their personal and professional experiences. The discussion themes of meetings enlarge the understanding of nature of water security in the region and extend what kind of actions or plan regarding the regional water security in the region and extend what kind of actions or plan regarding the regional water security should be formed and implemented in future. The emerged key strategies were handling salinity, looking into water level in water bodies, coordination between authorities and activities and lack of awareness among the communities on the potential water security among the different stakeholders. The spectrum of the respondents should be more inclusive and finding could be utilized for formulating a Provincial level drinking water policy in the future.
Keywords: multi – stakeholder; northern province; participatory approach; water management; water security